THE ROLE OF CHRISTIANITY IN OLD ENGLISH LITERATURE (Ustozlar uchun, 2025)
The importance of Christianity in Old English literature from the seventh to the eleventh centuries is examined in this article.  Literary output changed from mostly oral pagan traditions to written works produced mostly in monastery scriptoria during the Christianization of Anglo-Saxon England.  Christianity transformed Germanic culture's heroic ideals while also influencing literary themes, genres, symbolism, and linguistic forms.  This article demonstrates how Christian ideology and worldview influenced narrative patterns, moral viewpoints, and the notion of heroism through an analysis of key literature such as Beowulf, The Dream of the Rood, Caedmon's Hymn, homiletic writings, and bible translations.